Fearless Dominance/Boldness Is Not Strongly Related to Externalizing Behaviors: An Item Response-Based Analysis. (March 2021) - Crowe, Michael L.; Weiss, Brandon M.; Sleep, Chelsea E.; Harris, Alexandra M.; Carter, Nathan T.; Lynam, Donald R.; Miller, Joshua D.
There is substantial and ongoing debate regarding the centrality of Fearless Dominance/Boldness (FD/B) to psychopathic personality due, in part, to its generally weak relations with externalizing behaviors. In response to these findings, proponents of FD/B have offered two hypotheses. First, FD/B may have nonlinear associations with externalizing outcomes such that FD/B may lead to resilience at moderate levels, but an overabundance of FD/B will yield maladaptive behavioral outcomes. Second, FD/B may be related to antisocial outcomes when paired with high scores on other psychopathic traits such as self-centered impulsivity, meanness, or disinhibition. The current study tests these two possibilities using two large samples (Study 1: 787 undergraduates; Study 2: 596 Amazon's Mechanical Turk participants). An item response theory scoring approach particularly sensitive to curvilinearity was used to maximize our ability to find a true curvilinear effect, if present. No evidence in favor of the curvilinearity hypothesis was found. Only a single significant interaction predicting substance use was observed between boldness and meanness. These findings contribute to a growing literature raising concerns regarding the relevance of FD/B to psychopathy.